2013
DOI: 10.2310/jim.0000000000000003
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adropin Levels Predict Endothelial Dysfunction Like Flow-Mediated Dilatation in Patients With Type 2 Diabetes Mellitus

Abstract: Adropin is a new marker for use in demonstrating endothelial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…Several studies investigated a relationship between adropin level and cardiovascular complications in humans. Potential contribution of adropin to function of endothelial cells was reported by Topus et al [23]. This study reported that endothelial dysfunctions in patients with type 2 diabetes is paralleled by low levels of circulating adropin [23].…”
Section: Adropin In the Cardiovascular Systemmentioning
confidence: 67%
See 2 more Smart Citations
“…Several studies investigated a relationship between adropin level and cardiovascular complications in humans. Potential contribution of adropin to function of endothelial cells was reported by Topus et al [23]. This study reported that endothelial dysfunctions in patients with type 2 diabetes is paralleled by low levels of circulating adropin [23].…”
Section: Adropin In the Cardiovascular Systemmentioning
confidence: 67%
“…Potential contribution of adropin to function of endothelial cells was reported by Topus et al [23]. This study reported that endothelial dysfunctions in patients with type 2 diabetes is paralleled by low levels of circulating adropin [23]. An association between low levels of adropin and cardiovascular disorders was also reported.…”
Section: Adropin In the Cardiovascular Systemmentioning
confidence: 67%
See 1 more Smart Citation
“…This result suggests that the change in the serum adropin concentration may be one mechanism by which the exercise intervention improved vascular endothelial function in obese adolescents. Previous studies also demonstrated that a lower serum adropin level was associated with endothelial dysfunction using flow-mediated dilatation in patients with type-2 diabetes mellitus and metabolic syndrome 36 , 37 . Aerobic exercise training increased the serum adropin level and improved arterial stiffness and adiposity in obese adults 38 .…”
Section: Discussionmentioning
confidence: 83%
“…As previously reported (Jones et al, 1981a,b; Yang F. et al, 2016), our data also showed that water consumption in the 3700 m hypoxia group decreased > 40% at 1 day after 12 h water restriction as compared to the normoxia group, and the inhibition effect continued for at least 3 days (Figure 1E). We also tested adropin, which functions as a vascular protective factor in Type 2 diabetes patients and an inhibitor in the brain center of water drinking through an orphan G protein-coupled receptor 19 (GPR19; Topuz et al, 2013; Hu and Chen, 2016; Stein et al, 2016). Interestingly, our results showed that serum adropin was elevated under 3700 m hypoxia, and further increased in the 6000 m hypoxia group as compared to the moderate group (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%